Comparing on-site and off-site survey data to investigate survey biases in recreational fisheries data. (14th July 2021) - Lewin, Wolf-Christian; Weltersbach, Marc Simon; Haase, Kevin; Riepe, Carsten; Skov, Christian; Gundelund, Casper; Strehlow, Harry V
Abstract: Recreational fishing is increasingly included in fish stock assessments globally. Nonetheless, the extent and precision of recreational fisheries data are often limited. Common methods to collect those data are on-site and off-site surveys, both of which are prone to specific biases, whose magnitude is widely unknown. The present study compares data from an on-site access point intercept and a simultaneously conducted off-site diary survey, separately targeting charter boat, boat, and shore anglers in the German Baltic Sea recreational cod fishery to identify specific biases in the data sets. The analyses revealed indications of avidity and recall bias that might influence catch and release estimates. Catch rates and release rates differed substantially between the angling platforms. The catch and release rates of diarists and on-site anglers were in a similar range for every platform, and reasonably precise with standard errors between 0.1 and 0.4 fish per angler and day. Recreational fishing monitoring approaches should include complementary on-site surveys from time to time to control for biases whereby the angling platform should be taken into account. The low explanatory power of commonly collected socio-demographic variables indicated that variables capturing the heterogeneity of angler behaviour should additionally be included in future surveys.